Antibacterial activity of kelulut honey obtained from Kuala Pilah towards gram-positive and gram-negative bacteria / Siti Nurzalikha Nabilah Redzuan - Redzuan, Siti Nurzalikha Nabilah (Faculty of Applied Science, 2018)
Trigona honey in Malaysia which is known as Kelulut honey was produced by Trigona species or stingless bee. The aim of this study is to compare the antibacterial activity of kelulut honey obtained from Kuala Pilah towards gram positive and gram negative bacteria and to determine which concentration of honey have the highest antibacterial activity. Disc diffirsion (antibacterial activity) and Minimum Inhibitory Concentration $vIIC) methods were used during these studies. The t-test analysis on grarn positive bacteria display there is a significant different which is 0.028. Meanwhile, MIC shows no significant different, p more than 0.05. The finding from this research shows that kelulut honeys are not effective to inhibit gram positive and gram negative bacteria.